Implementing a Payment Gateway in the Mount Slamet Hiking Ticketing System - Bahy, Faishal; Arif, Dani; Amin, M. Syaiful (Politeknik Ganesha Medan, 2026)
Background—Many hiking basecamps in Indonesia still process bookings manually, causing queues, quota uncertainty, and errors in payment verification that hinder operations. Objective— Design and implement a web-based information system (e-ticketing) for Mount Slamet hiking, integrated with the Midtrans payment gateway; validate transactions in near-real-time and issue ticket IDs for gate inspection. Methods—Development followed Agile/Scrum. Requirements were gathered through observation and interviews; the design employed use-case, activity, ERD, and payment-flow models. Implementation used React (UI), Express and Prisma ORM (API), MySQL, and Midtrans Snap, with signature-verified, idempotent webhooks. Trials covered end-to-end black-box testing (booking; transitions among pending, paid, expired, and canceled; ticket-ID issuance; and check-in), cross-browser compatibility (Chrome, Edge, Firefox, Safari on desktop and mobile), and the System Usability Scale (SUS; n = 13). We also monitored propagation time from settlement to order update and behavior in the admin panel (route, quota, and date-closure management). Results—All functional scenarios passed; behavior was consistent across major browsers; mean SUS = 75.0 (> 68) indicates acceptable usability. Webhooks ensured automatic, duplicate-free status updates, with propagation on the order of seconds, so the reservation–payment–e-ticket chain operated end-to-end and was traceable via ticket-ID logs. Conclusion—The proposed e-ticketing system is technically feasible for basecamp operations and provides an architectural blueprint, core data schema, and a replicable Midtrans integration pattern. Future work will refine the public interface, add refund/void features, and conduct production-grade performance and security testing.